2020
DOI: 10.1002/jmv.25689
|View full text |Cite
|
Sign up to set email alerts
|

Updated understanding of the outbreak of 2019 novel coronavirus (2019‐nCoV) in Wuhan, China

Abstract: To help health workers and the public recognize and deal with the 2019 novel coronavirus (2019-nCoV) quickly, effectively, and calmly with an updated understanding. A comprehensive search from Chinese and worldwide official websites and announcements was performed between 1 December 2019 and 9:30 AM 26 January 2020 (Beijing time). A latest summary of 2019-nCoV and the current outbreak was drawn. Up to 24 PM, 25 January 2020, a total of 1975 cases of 2019-nCoV infection were confirmed in mainland China with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
1,102
9
73

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,299 publications
(1,273 citation statements)
references
References 12 publications
31
1,102
9
73
Order By: Relevance
“…However, the maximum latency of SARS-CoV-2 currently observed is as high as 24 days, which may increase the risk of virus transmission. Moreover, it also found that people 70 years or older had shorter median days (11.5 days) from the first symptom to death than those with ages below 70 years (20 days), demonstrating that elderly people have faster disease progression than younger people [27]. From the above, the public should pay more attention to elderly people who might be more vulnerable to the SARS-CoV-2.…”
Section: From the Perspective Of Viral Latencymentioning
confidence: 95%
See 2 more Smart Citations
“…However, the maximum latency of SARS-CoV-2 currently observed is as high as 24 days, which may increase the risk of virus transmission. Moreover, it also found that people 70 years or older had shorter median days (11.5 days) from the first symptom to death than those with ages below 70 years (20 days), demonstrating that elderly people have faster disease progression than younger people [27]. From the above, the public should pay more attention to elderly people who might be more vulnerable to the SARS-CoV-2.…”
Section: From the Perspective Of Viral Latencymentioning
confidence: 95%
“…From the epidemiological investigation report, elderly citizens are susceptible groups for SARS-CoV-2, the median age of death was 75 years, and most of them had comorbidities or a history of surgery before admission [27]. Zhong.…”
Section: From the Perspective Of Viral Latencymentioning
confidence: 99%
See 1 more Smart Citation
“…However, most deaths developed in male and elderly patients [4 , 40] . The median number of days from the appearance of the first symptom to death was 14 days, and it was significantly shorter among patients aged ≥70 years (11.5 days) compared with those aged < 70 years (20 days) ( P = 0.033) [40] .…”
Section: Discussionmentioning
confidence: 92%
“…The China National Health Commission reported the details of the first 17 deaths up to January 22, 2020. On January 25, 2020, a total of 1975 cases were confirmed to be infected with the COVID-19 in mainland China with a total of 56 deaths [8]. Another report on January 24, 2020 estimated the cumulative incidence in China to be 5502 cases [9].…”
Section: Introductionmentioning
confidence: 99%